Dielectric Properties of Iraqi Clay; Effect of Alumina Content - Abdul Sattar, Qasid; Hamadi, Talib Saloom (Nahrain University College of Engineering Journal, 2009)
In order to investigate the alumina effect on the low frequency dielectric constant of fire clay manufacture from Iraqi clay. Fire clay products have been powder ressed with different alumina content ,sintered ,then dielectric constant and dielectric loss( tan ) has been measured at low frequencies which extend from 30 kHz to 100kHz.There is a significant difference in their properties were observed between samples made with different alumina content added to the fire clay product where these differences were measured as a function of alumina content. This confirm that the insulating properties of the fire specimen from the electrical view point was affected by the crystallization of mullite and cristobolit